2022
DOI: 10.3390/life12020247
|View full text |Cite
|
Sign up to set email alerts
|

Ex-Vivo Preservation with the Organ Care System in High Risk Heart Transplantation

Abstract: Objective: Ex vivo organ perfusion is an advanced preservation technique that allows graft assessment and extended ex situ intervals. We hypothesized that its properties might be especially beneficial for high-risk recipients and/or donors with extended criteria. Methods: We reviewed the outcomes of 119 consecutive heart transplant patients, which were divided into two groups: A (OCS) vs. B (conventional). Ex vivo organ perfusion was performed using the Organ Care System (OCS). Indications for OCS-usage were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Interestingly, in OCS group 4 hearts were discarded because of an increasing lactate concentration and histological analysis revealed signs of infarction and contusion and severe unrecognized left ventricular hypertrophy 13 . Other singlecenter and retrospective studies [14][15][16][17][18][19][20] further reported graft ischemic time significantly shorter when grafts were preserved with NMP instead of being preserved with SCS, as reported in Table I. Therefore, the OCS could be an effective tool to ensure graft quality when the expected ischemic exceed the traditional threshold of 4 hours, favoring long-distance organ retrieval.…”
Section: To Shorten the Ischemic Timementioning
confidence: 94%
See 2 more Smart Citations
“…Interestingly, in OCS group 4 hearts were discarded because of an increasing lactate concentration and histological analysis revealed signs of infarction and contusion and severe unrecognized left ventricular hypertrophy 13 . Other singlecenter and retrospective studies [14][15][16][17][18][19][20] further reported graft ischemic time significantly shorter when grafts were preserved with NMP instead of being preserved with SCS, as reported in Table I. Therefore, the OCS could be an effective tool to ensure graft quality when the expected ischemic exceed the traditional threshold of 4 hours, favoring long-distance organ retrieval.…”
Section: To Shorten the Ischemic Timementioning
confidence: 94%
“…Heart MP could also play a protective role in high-risk recipients, particularly in those supported by durable mechanical circulatory support or who have undergone previous complex operations 14,18,20 . HTx in these patients might be technically demanding and often require a tedious dissection and prolonged cardiopulmonary bypass times to complete the removal of intrathoracic ventricular assist devices or the isolation of the cardiac structures.…”
Section: To Facilitate Htx In High-risk Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of heart transplant recipients has substantially improved over the past few decades, but preservation and optimization of the graft have not received the attention they deserve. OCS can be a gamechanger since the longer preservation time not only gives us the flexibility to carry out complex recipient dissections and analyze and manage the donor graft before transplant but it can also increase the pool of possible donors [27]. Listed below are the major advantages of using the OCS system for heart procurement.…”
Section: Comparison Of Ocs To Scsmentioning
confidence: 99%
“…Therefore, organ transport time and time required for complex mediastinal dissection and reconstruction significantly increases the cold ischemia time of the donor's heart even after it reaches the recipient's operating room. The OCS system becomes a savior in these situations, and surgeons can perform more peaceful and conscious mediastinal dissection [27]. Fleck et al in their study found that pediatric transplant patients had better outcomes when the donor heart was perfused with OCS than those in which SCS was used [33].…”
Section: Advantagesmentioning
confidence: 99%